2010
DOI: 10.1002/jbmr.147
|View full text |Cite
|
Sign up to set email alerts
|

Development of a novel transdermal patch of alendronate, a nitrogen-containing bisphosphonate, for the treatment of osteoporosis

Abstract: Bisphosphonates are widely used for the treatment and prevention of bone diseases, including Paget disease, hypercalcemia of malignancy, and postmenopausal osteoporosis. In this study, we developed a novel transdermal patch of alendronate, a nitrogencontaining bisphosphonate, for the treatment of bone diseases. The maximum permeation fluxes of alendronate through rat and human skin after application of this patch were 1.9 and 0.3 mg/cm 2 per hour, respectively. The bioavailability (BA) of alendronate in rats w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 42 publications
0
14
0
1
Order By: Relevance
“…It is indicated that the transdermal permeation of ALD using this patch system was sufficient for the treatment of bone diseases. The plasma calcium level was effectively reduced after application of the ALD patch in 1a-hydroxyvitamin D 3 -induced hypercalcemia model rats (Kusamori et al, 2010). These results indicated that the developed transdermal delivery system of ALD is a promising approach that would improve therapeutic effects and better compliance and QOL (quality of life) in patients undergoing treatment for OP.…”
Section: Transdermal Delivery (Td)mentioning
confidence: 74%
“…It is indicated that the transdermal permeation of ALD using this patch system was sufficient for the treatment of bone diseases. The plasma calcium level was effectively reduced after application of the ALD patch in 1a-hydroxyvitamin D 3 -induced hypercalcemia model rats (Kusamori et al, 2010). These results indicated that the developed transdermal delivery system of ALD is a promising approach that would improve therapeutic effects and better compliance and QOL (quality of life) in patients undergoing treatment for OP.…”
Section: Transdermal Delivery (Td)mentioning
confidence: 74%
“…Biophophonates are carbon-substituted pyrophosphate analogues that exhibit high affinity for hydroxyapatite, inhibit bone resorption, and used in the treatment and prevention of bone disease [49]. Alendronate sodium, a nitrogen-containing bisphosphonate, is widely used for the prevention and treatment of osteoporosis.…”
Section: The Biomarkers and Their Potential Values In Osteoporosismentioning
confidence: 99%
“…Transversely cut tracheae were repaired with surgical sutures after a single intrapulmonary administration. The tibia bone structures of these rats under pentobarbital anesthesia were evaluated by X‐ray microcomputed tomography (µCT) (Rigaku, Tokyo, Japan) 8 weeks after the OVX operation; µCT was performed as described previously 22…”
Section: Methodsmentioning
confidence: 99%